(untitled) (Biodiversitas Journal of Biological Diversity, 2016)
Sulawesi is the largest island in Wallacea region and a biogeographically unique area. The island is very rich in endemic species, worldwide known only known from Sulawesi. Nevertheless, scientific knowledge of the plants of Sulawesi is still limited and there is a lack of botanical exploration and publications. In 2000, Tadulako University of Palu with support of the German Research Foundation (DFG), the Universities of GÃ¶ttingen and Leiden and the Herbarium Bogoriense, has constructed a herbarium, the Herbarium Celebense. The herbarium has been registered in the International Index Herbariorum (New York) with the abbreviation CEB. The Herbarium Celebense contains about 3000 plant specimens, especially from Central Sulawesi and mainly spermatophytes and pteridophytes. This article reviews the current knowedge of plant diversity of the Sulawesi and Wallacea bioregion as a basis for the conservation of its rich flora. ïƒ£ 2004 Jurusan Biologi FMIPA UNS Surakarta Key words: central Sulawesi, Wallacea bioregion, flora, biogeography, plant diversity, endemic plants.